2015
DOI: 10.1017/jfm.2015.249
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulations of stratified turbulence: the dynamic Smagorinsky model

Abstract: The dynamic Smagorinsky model for large eddy simulation (LES) of stratified turbulence is studied in this paper. A maximum grid spacing criterion of ∆/L b < 0.24 is found in order to capture several of the key characteristics of stratified turbulence, where ∆ is the filter scale and L b is the buoyancy scale. These results show that the dynamic Smagorinsky model needs a grid spacing approximately twice as large as the regular Smagorinsky model to reproduce similar results. This improvement on the regular Smago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…'). Recent work on large eddy simulation of stratified turbulence has shown that eddy viscosity models without any explicit Ri dependence work well as long as L b is sufficiently resolved (Khani andWaite 2014, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…'). Recent work on large eddy simulation of stratified turbulence has shown that eddy viscosity models without any explicit Ri dependence work well as long as L b is sufficiently resolved (Khani andWaite 2014, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Information about the dynamics of the local energy transfer is therefore lost, and in practice, the averaging procedure removes the local effect of backscatter, because the averaged c s is usually positive (e.g. [7,[9][10][11][12]). …”
Section: Introductionmentioning
confidence: 99%
“…The performance of different eddy viscosity SGS models (the Smagorinsky, dynamic Smagorinsky and Kraichnan models) has recently been studied in LES of stratified turbulence with isotropic grid resolution [10,22]. In all cases, it is shown that LES must resolve the buoyancy scale L b = 2π u rms /N to capture the fundamental large scale characteristics of stratified turbulence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations